Busy Urban Soundscape Underwater: Acoustic Indicators vs. Hydrophone Data - Kamil Monastyrski; Grzegorz Chrobak; Rengin Aslanoğlu; Jacob Wilkerson; Jan K. Kazak (Urban Science)
Urban noise pollution extends into aquatic environments, influencing underwater ecosystems. This study examines the effectiveness of acoustic indicators in characterizing urban underwater soundscapes using hydrophone recordings. Three indices, the Acoustic Complexity Index (ACI), Acoustic Diversity Index (ADI), and Normalized Difference Soundscape Index (NDSI), were analyzed to assess their ability to distinguish anthropogenic and natural acoustic sources. The results indicate that the ACI tracks urban noise fluctuations, particularly from vehicles and trams, while the ADI primarily reflects transient environmental interferences. The NDSI, while designed to differentiate biophony from anthropogenic noise, proves unreliable in urban underwater settings, often misclassifying noise sources. These findings highlight the limitations of traditional acoustic indices in urban aquatic environments and emphasize the need for refined methods to improve hydrophone data interpretation. Thus, this study aims to understand the acoustic indicators’ interactions with underwater urban noise, which is crucial for enhancing environmental monitoring and noise mitigation strategies.